INTERPOLATION ALGORITHM IN SOLAR PANEL LIGHT ABSORPTION - Ihsanurrizqie Indra Siregar (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
This study describes the increase in light energy that occurs on the surface of the solar panel or photovoltaic (PV) using a sensor distribution where the data is processed by the cubic spline interpolation method so that it can be used to determine the position of the solar panels which are effective and ideal for receiving sunlight. so that you get information about the power released by the solar panels. The mapping of heat distribution on PV panels uses the cubic spline interpolation method, which results from the interpolation and experimental results showing the PV panel in a vertical position with a slope of 0º at 12.00-14.00 produces the highest current, namely 449.2mA with a voltage generated of 1.03V resulting in a power of 0.46W This is more optimal than the PV surface temperature which is hotter in the vertical position with a slope of 45º or the horizontal position of 0º and 45º at the same hour.